Critical assessment of the linear market model in the Johannesburg inner city - Nemaungani, Livhalani Salome (My University, 2017)
The linear market model is the City of Johannesburg’s most recent street trading developmental intervention intended to manage and locate street traders in highly pedestrianised streets. The inner city of the City of Johannesburg is known for receiving a high influx of migrants from inside South Africa and outside the country seeking economic opportunities. Some of these migrants find themselves in the streets of the City of Johannesburg engaging in illegal street trading. The City of Johannesburg municipality has come up with various strategies to regulate and manage street trading including the introduction of By-laws. In 2008 the City of Johannesburg municipality introduced the linear market model as a means to provided proper structures for street traders, and models that are intended to organise them and assist in unlocking their entrepreneurial skills. The implementation of the linear market model had its own challenges, including some stakeholders believing that it is not beneficial and some traders believing that the entire process of moving them around undermined their rights. However, this research had not examined the conflicts that the municipality has with the street traders but focused on assessing the situation relating to the market, street traders’ challenges and the support they receive from the municipality. This research was conducted in the form of a case study to critically assess the linear markets located in the inner city of one of the busiest cities of the continent. The research assessed the functionality of the model focusing on the benefits that this market model brought to the street traders. The methodology applied to carry out this research does not generalise the findings for broader scope and consideration. However, the significance of the outputs through this research could be of use to provide insights within the City of Johannesburg where such infrastructure is developed. The research found that the linear market model is structurally functional but with some administration challenges. Maintenance and inadequate support by the municipality was the main challenge in these markets. This research study made recommendations to assist the municipality as it implements the linear market model in other regions of the municipality.
Dissertation presented in partial fulfilment for the degree of Master of Management (in the field of Public and Development Management) to the Faculty of Commerce, Law and Management, University of the Witwatersrand September 2017
Keywords: Street vendors; Informal sector (Economics)|zSouth Africa